Scope and Limits of Teriparatide Use in Delayed and Nonunions: A Case Series - Ismailidis, Petros (Clin Pract, 2021)
Nonunion is known to occur in up to 10% of all bone fractures. Until recently, the treatment options considered in cases of delayed union and nonunion focused on revision surgery and improvement of local healing. Lately, teriparatide has been introduced as an osteoanabolic factor that induces fracture healing in cases with delayed or nonunions. We report on a series of five cases of delayed and nonunions treated with teriparatide: delayed unions of an atypical femoral fracture, of a multifragmentary clavicle fracture, and of a periprosthetic humeral fracture; nonunion of a tibial and fibular fracture; and infected nonunion of a tibial and fibular fracture. Based on this series, the indications and limits of application of teriparatide in cases of impaired fracture healing are discussed. Due to the “off-label” character of this application, informed consent, and cost coverage from the healthcare insurance must be obtained prior to treatment. In our experience and according to the limited existing literature, teriparatide is a safe feasible treatment in cases of delayed and nonunions with a reasonable need of resources. While adequate biomechanical stability remains the cornerstone of fracture healing, as well as healing of nonunions, teriparatide could help avoid repetitive surgeries, especially in atrophic delayed and nonunions, as well as in patients with impaired fracture healing undergoing bisphosphonate therapy. There is an urgent need for widely accepted definitions, standardized protocols, as well as further clinical trials in the field of impaired fracture healing.